Improving Critical Thinking Skills of High School Students through STEM-Based PBL LKPD on Global Warming Materials - Chelsy Wardani Putri; Eko Hariyono; Yuni Sri Rahayu; Satriawan, Muhammad (Jurnal Perspektif, 2025)
The critical thinking skills of students in schools on global warming materials have not improved. This study aims to analyze the effectiveness of STEM-based PBL (science, technology, engineering, mathematic) LKPD in improving students' critical thinking skills, especially on global warming materials. The research method used was an experiment with a one-group pretest-posttest design involving 36 students of class X of SMA Negeri Kesamben Jombang. The results of the study showed that there was a significant increase in students' critical thinking skills after implementing STEM-based PBL learning on global warming materials. The average pretest score of 45.72 increased to 79.89 in the posttest with an average N-Gain score of 0.742 which showed an increase of 74.22% with the high category in 21 students, 11 students in the medium category and 4 students in the low category. The STEM approach is implemented in physics learning with the aim of not only improving critical thinking skills but also helping students in developing 21st century skills.